The Pricing puzzle: The default term structure of collateralised loan obligations - Andreas A. Jobst (Goethe University Frankfurt, Center for Financial Studies (CFS), 2002)
Ambivalence in the regulatory definition of capital adequacy for credit risk has recently steered the financial services industry to collateral loan obligations (CLOs) as an important balance sheet management tool. CLOs represent a specialised form of Asset-Backed Securitisation (ABS), with investors acquiring a structured claim on the interest proceeds generated from a portfolio of bank loans in the form of tranches with different seniority. By way of modelling Merton-type risk-neutral asset returns of contingent claims on a multi-asset portfolio of corporate loans in a CLO transaction, we analyse the optimal design of loan securitisation from the perspective of credit risk in potential collateral default. We propose a pricing model that draws on a careful simulation of expected loan loss based on parametric bootstrapping through extreme value theory (EVT). The analysis illustrates the dichotomous effect of loss cascading, as the most junior tranche of CLO transactions exhibits a distinctly different default tolerance compared to the remaining tranches. By solving the puzzling question of properly pricing the risk premium for expected credit loss, we explain the rationale of first loss retention as credit risk cover on the basis of our simulation results for pricing purposes under the impact of asymmetric information.
urn:nbn:de:hebis:30-10048
Keywords: C15; C22; D82; F34; G13; G18; G20; 330; Loan securitisation; CLO; structured finance